A fine-grained parallel algorithm for the cyclic flexible job shop problem - Bożejko, Wojciech; Pempera, Jarosław; Wodecki, Mieczysław (Archives of Control Sciences, 2017)
Abstract In this paper there is considered a flexible job shop problem of operations scheduling. The new, very fast method of determination of cycle time is presented. In the design of heuristic algorithm there was the neighborhood inspired by the game of golf applied. Lower bound of the criterion function was used in the search of the neighborhood.